Confirmation of papillary thyroid cancer susceptibility loci identified by genome-wide association studies of chromosomes 14q13, 9q22, 2q35 and 8p12 in a Chinese population. Issue 10 (11th July 2013) - Wang, Yu-Long; Feng, Shou-Hao; Guo, Shi-Cheng; Wei, Wen-Jun; Li, Duan-Shu; Wang, Yu; Wang, Xiaofeng; Wang, Zhuo-Ying; Ma, Yan-Yun; Jin, Li; Ji, Qing-Hai; Wang, Jiu-Cun
Abstract : Background: Five single nucleotide polymorphisms (SNPs) were previously reported to be associated with thyroid cancer in European populations in two genome-wide association studies (GWAS): rs965513 (9q22.33), rs944289 (14q13.3), rs116909374 (14q13.3), rs966423 (2q35) and rs2439302 (8p12). Only the first two SNPs have been validated in independent populations and none were replicated in Chinese populations. Methods: The above five SNPs were genotyped in 845 papillary thyroid cancer (PTC) and 503 benign thyroid tumour (BN) patients and 1005 controls in a Chinese population using the SNaPshot multiplex single nucleotide extension system. Results: Significant associations were detected among PTC and rs944289 (p=8.007e-11), rs965513 (p=1.013e-4), rs966423 (p=1.688e-3) and rs2439302 (p=1.096e-4) in a dominant model, while the rs116909374 SNP was not detected in the Chinese population. The PTC risk increased with rise in accumulative numbers of risk alleles carried by individuals (p=5.929e-13). The PTC OR of carriers of six risk alleles (1.4% of the control population) was 23.587 compared with non-risk homozygotes (1.0% of the control population, with zero risk alleles). No individuals were homozygous for all the four SNPs (carriers of eight risk alleles) and only three PTC cases were carriers of seven risk alleles. A significant association between 14q13.3 SNP rs944289T and BN was also found (p=0.0014). Conclusions: Four candidate loci, rs965513 (9q22.33), rs944289 (14q13.3), rs966423 (2q35) and rs2439302 (8p12), identified by GWAS for PTC risk were confirmed in a Chinese population. The PTC risk of accumulative risk allele carriers increased with the number of risk alleles.